(untitled) (Fiep Bulletin - online, 2012)
The objective of this study was to evaluate the stature of schoolchildren of both sexes with age between 10 and 15years. The sample consisted of 469 schoolchildren of both sexes of 10 and 15 years, voluntarily chosen, being 211 males and 258females enrolled in municipal schools in the city of Arapiraca - AL in 2009. To collect data we used a stadiometer and protocol citedby Petroski (2003). For the treatment of the data was used statistics of central tendency, and then seeks to include the totalnumber of possibilities for comparison of stature between the ages by sex, we used the method of analysis of variance (ANOVAONE WAY), and to verify the existence of gender differences by age, we used the Student t test for independent samples. Finally,to identify possible differences in the comparisons was used post hoc Tukey procedure. The level of significance was set at ? ?0,05. The results show that both the male students, and females are within normal limits in relation to the growth curves proposedby WHO (2007). It was also observed that there were significant differences in the comparative analysis for height between agesand between sexes by age. It is concluded that the results corroborate the statements and findings in the existing literature inrelation to current growth spurt.